CULTURAL LEADERSHIP IN INTERNATIONAL EDUCATION CROSS INSTITUTIONS - Ergasheva Ozodabonu Bahodirjon qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: As international education institutions grow in number and influence, the role of cross-cultural leadership becomes increasingly vital. Effective leaders must navigate cultural diversity among students, faculty, and administrators while promoting inclusive environments that support global learning. This article examines the key competencies, challenges, and strategies of cross-cultural leadership in higher education settings. Through literature analysis and global case references, it explores how culturally responsive leadership contributes to institutional success and intercultural collaboration.